1975
DOI: 10.1128/iai.11.3.517-525.1975
|View full text |Cite
|
Sign up to set email alerts
|

Superficial antigens of Campylobacter (Vibrio) fetus: characterization of antiphagocytic component

Abstract: A glycoprotein responsible for the antiphagocytic properties of Campylobacter fetus has been identified by comparing cells of a wild-type strain with those of a mutant lacking this substance. The antiphagocytic component is demonstrable through electron microscopy as a discrete, negatively charged structure on the periphery of the cell. CLT is readily removed from the cell by mild extraction procedures and contributes to the inagglutinability in O antiserum normally displayed by C. fetus. Cells possessing this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(81 citation statements)
references
References 8 publications
6
75
0
Order By: Relevance
“…Incubation with semm selects for strains that express S-layer proteins because the proteins protect against complement-mediated killing (Blaser and Pei, 1993), Second, revertants that express full-length S-layer proteins show no expression of the truncated 50 kDa protein, indicating a switch in expression locus. Third, although spontaneous S-layer vahants of wild-type strains have been previously observed (McCoy et a!., 1975;Blaser et al, 1987;Dubreil etal., 1988), the current observations suggest that wild-type C. fetus strains have the intrinsic ability for high-frequency variation of S-layer proteins, but this phenomenon may not be readily evident (or quantifiable) in the absence of a means for selection. Electron microscopic study of mutant strain 23D:401:5 indicated that approximately 1 cell in 50 exhibited an S-layer, confirming lack of export of the truncated protein, and confinning the high-frequency of reversion.…”
Section: Discussionmentioning
confidence: 97%
“…Incubation with semm selects for strains that express S-layer proteins because the proteins protect against complement-mediated killing (Blaser and Pei, 1993), Second, revertants that express full-length S-layer proteins show no expression of the truncated 50 kDa protein, indicating a switch in expression locus. Third, although spontaneous S-layer vahants of wild-type strains have been previously observed (McCoy et a!., 1975;Blaser et al, 1987;Dubreil etal., 1988), the current observations suggest that wild-type C. fetus strains have the intrinsic ability for high-frequency variation of S-layer proteins, but this phenomenon may not be readily evident (or quantifiable) in the absence of a means for selection. Electron microscopic study of mutant strain 23D:401:5 indicated that approximately 1 cell in 50 exhibited an S-layer, confirming lack of export of the truncated protein, and confinning the high-frequency of reversion.…”
Section: Discussionmentioning
confidence: 97%
“…The method followed was a modification of that described by McCoy et al (1975). Stationary-phase cells grown microaerobically at 37°C in Mueller-Hinton medium supplemented with 20 mM sodium pyruvate, were harvested by centrifugation at 6000× g at room temperature, the cell pellet was washed twice with distilled water, and then resuspended in 100 ml of 0.2 M glycine-hydrochloride buffer (pH 2.2) per 4 g of packed cells.…”
Section: Acidic Glycine Extraction Of Surface Proteinsmentioning
confidence: 99%
“…Immunoglobulin G and IgA anti-campylobacter antibodies in serum and saliva were measured by ELISA. Previous investigations [10] have showed that the acid-glycine extractable antigens (AE) [11] of C. jejuni strain 81116 provides a suitable capture antigen for such studies. The use of a single strain ensures that antibodies directed largely against common campylobacter antigens are detected.…”
Section: Enzyme-linked Immunosorbent Assays (Elisa)mentioning
confidence: 99%